2013
DOI: 10.1007/s00268-013-2330-0
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Impact of Repeat Biopsy for Follicular Lesion/Atypia of Undetermined Significance

Abstract: Repeat biopsy was underutilized in FLUS/AUS cases. Repeat biopsy allows a significant proportion of FLUS/AUS patients without other indications for surgery to move to surveillance. In patients who have indications for thyroidectomy regardless of FLUS/AUS results,repeat biopsy does not appear necessary. Malignancy and thyroidectomy rates were similar among patients who did or did not have a repeat biopsy. Further data must be obtained to determine the long-term outcomes for surveillance of FLUS/AUS lesions in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 20 publications
5
61
1
Order By: Relevance
“…2,14 We found that the incidence of AUS/FLUS on repeated FNAB (42.5%) is within the range of previously published data of 20 to 48.5%, 4,8,12,14 and that the risk of malignancy in two consecutive AUS/FLUS was 50%, higher than most published data of 13.5 to 43%. 4,7,8,14 Our data support the significant benefit of repeating FNAB in triaging patients with AUS/FLUS; those who have a diagnosis of malignancy or follicular neoplasm/ suspicious for follicular neoplasm should undergo surgery. In our patients, the risk of malignancy in benign diagnoses after the second FNAB was 27.3%, which is close to what was published by Vanderlaan (29%).…”
Section: Discussioncontrasting
confidence: 39%
See 3 more Smart Citations
“…2,14 We found that the incidence of AUS/FLUS on repeated FNAB (42.5%) is within the range of previously published data of 20 to 48.5%, 4,8,12,14 and that the risk of malignancy in two consecutive AUS/FLUS was 50%, higher than most published data of 13.5 to 43%. 4,7,8,14 Our data support the significant benefit of repeating FNAB in triaging patients with AUS/FLUS; those who have a diagnosis of malignancy or follicular neoplasm/ suspicious for follicular neoplasm should undergo surgery. In our patients, the risk of malignancy in benign diagnoses after the second FNAB was 27.3%, which is close to what was published by Vanderlaan (29%).…”
Section: Discussioncontrasting
confidence: 39%
“…This will justify the continued surveillance in patients who otherwise do not have an indication for surgical intervention. Similar conclusions were made by Broome et al 4 and Chen et al 6 The latter authors advised to repeat FNAB after 3 to 6 months, and if the repeated biopsy is nondiagnostic or again interpreted as AUS/FLUS, then surgery is indicated. On the contrary, some authors observed that no difference in malignancy rate between one and repeated FNABs.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…although re-FNA diagnosis is more precise, about 20% -25% of nodules repeatedly receive the results of AUS/FLUS (12) which end up with inaccurate judgment. Also, the malignancy rates associated with AUS/FLUS with or without repeat FNAB have been reported with variable results in different series (7,11,(13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%